Obstructive Granulomatous Bronchiolitis Obliterans due to Mycobacterium tuberculosis - Agarwal, R.; Kumar, V.; Jindal, S.K. (Monaldi Archives for Chest Disease, 2005)
Bronchiolitis obliterans is an uncommon cause of obstructive airway disease in adults characterised by progressive irreversible airway obstruction. Granulomatous bronchiolitis is a rare entity and tuberculosis presenting as bronchiolitis is distinctly uncommon. The authors present a case of tubercular granulomatous bronchiolitis obliterans, confirmed on histopathology, who responded completely to anti-tubercular chemotherapy.